2012
DOI: 10.3945/ajcn.111.026278
|View full text |Cite|
|
Sign up to set email alerts
|

Replacing caloric beverages with water or diet beverages for weight loss in adults: main results of the Choose Healthy Options Consciously Everyday (CHOICE) randomized clinical trial

Abstract: Background: Replacement of caloric beverages with noncaloric beverages may be a simple strategy for promoting modest weight reduction; however, the effectiveness of this strategy is not known.Objective: We compared the replacement of caloric beverages with water or diet beverages (DBs) as a method of weight loss over 6 mo in adults and attention controls (ACs).Design: Overweight and obese adults [n = 318; BMI (in kg/m2): 36.3 ± 5.9; 84% female; age (mean ± SD): 42 ± 10.7 y; 54% black] substituted noncaloric be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
300
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(311 citation statements)
references
References 46 publications
4
300
0
7
Order By: Relevance
“…Therefore, interventions aimed at reducing added sugar intake should focus on these foods, especially sugar-sweetened beverages. As sugar-sweetened beverages contributed to half of the added sugar among consumers, reducing the consumption of sugar-sweetened beverages, such as by replacement with water or other low-energy beverages (40,41) , may lead to a considerable decrease in added sugar intake in the Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interventions aimed at reducing added sugar intake should focus on these foods, especially sugar-sweetened beverages. As sugar-sweetened beverages contributed to half of the added sugar among consumers, reducing the consumption of sugar-sweetened beverages, such as by replacement with water or other low-energy beverages (40,41) , may lead to a considerable decrease in added sugar intake in the Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of those studies, though, does not differ overall from studies in which participants were not blinded to the intervention (e.g., 39,55) , indicating that in the context of attempted weight loss the effect of LCS is not undermined by awareness of LCS consumption. However, further research would be useful.…”
Section: Conjecture: Exposure To Sweetness Increases Desire For Sweetmentioning
confidence: 89%
“…The one study (the CHOICE trial) that has looked at this found slightly, but not significantly, greater weight loss in the group switching to LCS (39) .…”
Section: Conjecture: Exposure To Sweetness Increases Desire For Sweetmentioning
confidence: 96%
“…11,12 In contrast, drinking plain water instead of SSBs is one approach for individuals trying to reduce dietary energy intake and thereby possibly benefit obesity prevention and control. [13][14][15] Hence, consuming water as part of a healthy diet (eg, one that contains fruits, vegetables, whole grains, low-fat/reduced fat dairy, and lean meats) can aid weight management [13][14][15][16] and, if substituted for SSB consumption, also possibly avert the adverse consequences associated with SSB intake such as dental caries, 6 and avoid risks from high levels of SSBs such as developing obesity [2][3][4][5] and type 2 diabetes. 7 One approach for promoting water intake is to make free potable drinking water widely accessible in public facilities, including schools.…”
Section: Introductionmentioning
confidence: 99%